2023
DOI: 10.3390/ijms24108460
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiota–Gut–Brain Axis in Behaviour and Brain Disorders

Abstract: The gut, along with its microbiota (MB-gut), is the largest absorption organ and reservoir of bacteria in the human body [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…However, the concentration of acetylcholine in faeces steadily increased during and after pregnancy. Previous studies have indicated that the gut microbiota can influence the central nervous system by synthesising neuroactive compounds or regulating the secretion of neurotransmitters, such as acetylcholine, to regulate cognition [ 50 , 51 ]. In this study, the abundance of Flavonifractor was positively correlated with the faecal acetylcholine level.…”
Section: Discussionmentioning
confidence: 99%
“…However, the concentration of acetylcholine in faeces steadily increased during and after pregnancy. Previous studies have indicated that the gut microbiota can influence the central nervous system by synthesising neuroactive compounds or regulating the secretion of neurotransmitters, such as acetylcholine, to regulate cognition [ 50 , 51 ]. In this study, the abundance of Flavonifractor was positively correlated with the faecal acetylcholine level.…”
Section: Discussionmentioning
confidence: 99%